Assessment of phenotypic variation of winter barley in Scandinavia - Ortíz, R.; Mohamed, S.F.; Madsen, S.; Weibull, J.; Christiansen, J.L. (Informa UK Limited, 2001)
Phenotypic diversity for agronomic characteristics was determined in an experiment without fertilizer in 1998 in 41 two-row and 21 six-row winter barley accessions, provided by the Nordic Gene Bank, at Højbakkegård (Denmark). There were significant differences among these 62 accessions for spring establishment, early flowering, covering, plant height, lodging, tillering, spike length, number of kernels per spike and thousand kernel weight. On average, two-row barley accessions had better establishment, covering and standability (although they were slightly taller) but showed lower tillering than six-row barley accessions. Two-row barley accessions also had larger spikes with fewer kernels, but heavier weight, than six-row barley accessions. There were significant phenotypic correlations among the characteristics scored. However, not all of them were common to two- and six-row barley accessions, which suggests the evolution of distinct genetic systems controlling these associations in the two sets of barley accessions. Average linkage cluster analysis and principal component analysis confirmed number of rows as an important characteristic to discriminate among cultivated barley accessions.